A novel harmonic mitigator-based 12-pulse rectification for vector-controlled induction motor drives. (3rd January 2006) - Singh, Bhim; Bhuvaneswari, G.; Garg, Vipin
This paper presents an optimised 12-pulse autotransformer-based AC–DC converter with reduced kVA magnetics for reducing the harmonic distortion in AC mains current in a vector-controlled induction motor drive (VCIMD). The proposed AC–DC converter results in elimination of fifth, seventh and 11th harmonics in the supply current. The proposed system consists of an autotransformer and a tuned passive filter. A small rating passive filter is tuned to 11th harmonic frequency and it reduces the harmonic currents generated by the AC–DC converter, thus reducing the total harmonic distortion of AC mains current. The filter is tuned such that the supply current is less than the converter input AC current. The detailed simulations of the drive system along with the 12-pulse AC–DC converter are carried out in MATLAB environment using SIMULINK and power system blockset toolboxes. Four different topologies of 12-pulse autotransformer connections have been considered to feed voltage source inverter-based VCIMD. A set of power quality parameters such as total harmonic distortion and crest factor of AC mains current, power factor, displacement factor and distortion factor at AC mains and DC bus ripple factor for a VCIMD fed from different 12-pulse converters are computed and tabulated. The effect of load on VCIMD is also studied to demonstrate the effectiveness of the proposed topology for power quality improvement of AC mains.